2002
DOI: 10.1038/sj.bjc.6600264
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes in the expression of human colonic nutrient transporters during the transition from normality to malignancy

Abstract: Healthy colonocytes derive 60 -70% of their energy supply from short-chain fatty acids, particularly butyrate. Butyrate has profound effects on differentiation, proliferation and apoptosis of colonic epithelial cells by regulating expression of various genes associated with these processes. We have previously shown that butyrate is transported across the luminal membrane of the colonic epithelium via a monocarboxylate transporter, MCT1. In this paper, using immunohistochemistry and in situ hybridisation histoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
4
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 41 publications
6
83
4
2
Order By: Relevance
“…Unexpectedly, when analysing MCT expression in the available adjacent normal epithelium, we found that MCT1 was the least expressed isoform. However, since these normal tissue areas are in the surroundings of tumour cells, we cannot rule out the possibility that these areas are under the influence of [12,14,17]. Our immunohistochemical findings are in agreement with the results of Koukourakis et al [12].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Unexpectedly, when analysing MCT expression in the available adjacent normal epithelium, we found that MCT1 was the least expressed isoform. However, since these normal tissue areas are in the surroundings of tumour cells, we cannot rule out the possibility that these areas are under the influence of [12,14,17]. Our immunohistochemical findings are in agreement with the results of Koukourakis et al [12].…”
Section: Discussionsupporting
confidence: 83%
“…Although using different antibodies from this previous study, we were also able to detect a high percentage of positive cases for MCT1 expression as well as MCT1 plasma membrane expression in a high number of cases. However, these findings diverge from previous reports, where the authors described a decrease in MCT1 expression in CRC during transition from normality to malignancy [14,17]. Concerning the clinico-pathological data, we found a significant correlation between MCT1 plasma membrane staining and vascular invasion.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In a related, unpublished study, SLC16A1 expression was significantly altered, and therefore the test was also used to verify the expression in the jejunum in this study. SLC16A1 (fc: 21.87, DON5) had a decreased expression in the jejunum, and it transports monocarboxylates such as butyrate, lactate and pyruvate (Lambert et al, 2002). It has been suggested that effects of DON on membrane transport is a result of specific modulation of the transporters and is not due to cell damage (Maresca et al, 2002), which is supported by our observations, especially because SLC7A10 was upregulated.…”
Section: Nutrient Transportsupporting
confidence: 85%
“…Pinheiro and colleagues reported increased expression of MCTs 1, 2, and 4 in colorectal carcinomas (8). However, earlier analysis of healthy colonic tissues and carcinomas revealed a significant decline in MCT1 protein expression during transition from normality to malignancy (9).…”
Section: Introductionmentioning
confidence: 99%